2013
DOI: 10.1080/1068316x.2012.684058
|View full text |Cite
|
Sign up to set email alerts
|

Cost and benefit of a new instruction for the cognitive interview: the open depth instruction

Abstract: The quality and the quantity of information recalled by eyewitnesses during a criminal investigation is of crucial importance. To increase the volume of details recalled during an interview, the cognitive interview recommends using various retrieval strategies to enhance recall. We tested a new retrieval instruction, the open depth (OD) instruction. The efficacy of this new instruction was assessed with the number of unit of information and the accuracy rate. We also assessed the cost-and-benefit of this new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Research on the benefits of the CI for recall has mostly focused on the effectiveness of the different mnemonics rather than on the use of prompts following an initial narrative (e.g. Brunel, Py, & Launay, 2013;Colomb & Ginet, 2012;Memon, Wark, Bull, & Koehnken, 1997;Paulo, Albuquerque, & Bull, 2013). Similar to the use of cues, asking follow-up questions can also further prompt interviewees to search through their memory (Fisher & Geiselman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the benefits of the CI for recall has mostly focused on the effectiveness of the different mnemonics rather than on the use of prompts following an initial narrative (e.g. Brunel, Py, & Launay, 2013;Colomb & Ginet, 2012;Memon, Wark, Bull, & Koehnken, 1997;Paulo, Albuquerque, & Bull, 2013). Similar to the use of cues, asking follow-up questions can also further prompt interviewees to search through their memory (Fisher & Geiselman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Davis, McMahon, and Greenwood (2005) compared the change order and change perspective mnemonics with free recall attempts and found no advantage of both ECI mnemonics in comparison with free recall tasks. Brunel, Py, and Launay (2013) found that using the open depth instruction (asking participants to focus their attention on the small details while recalling the event once again) instead of the change perspective mnemonic allowed the interviewer to obtain more information. Dando, Ormerod, Wilcock, and Milne (2011) found that recalling in reverse order might be less effective in comparison with another free recall regarding the number and accuracy of recalled units of information.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, contrary to Vrij et al (2008), the change of order instruction did not allow an increase in discrimination between truthful and fallacious narrations. In the same way, Launay, Py and Brunel (2011) showed that one could increase discrimination between truthful and fallacious narrations (with the use of CBCA criteria) with a second recall using an open-depth instruction (Brunel et al, 2012). Finally, Vrij et al (2010) showed that the use of drawing (a technique recommended by Dando, Wilkock and Milne, 2009, in place of the mental reinstatement during the CI) allowed 80% of truthful narrations and 87% of fallacious narrations to be correctly categorized.…”
Section: Assessing Eyewitness Veracitymentioning
confidence: 89%
“…Knowing that the perception of time is relative, one can question the perception of the CI from the interviewer's point of view. Recently, Brunel, Py and Launay (2012) proposed new indicators which aim at measuring the costs and benefits associated with various free recalls within the CI by testing divers instructions. They measured the proportion of repeated information obtained during additional free recalls.…”
Section: Costs Of the CImentioning
confidence: 99%
See 1 more Smart Citation